DEVELOPMENT AND SELF-DEVELOPMENT OF THE FORMING PERSONALITY IN THE CONTEXT OF MODELING ACTIVITIES - M. A. Frizen (Вестник Кемеровского государственного университета, 2015)
The paper analyzes the activity contexts of the personality development connected with social reality modeling (direct and emotional communication in infancy, communication of preschool children of the same age in subject roleplaying games and communication with the reference environment at teenage age), the potential for their personal selfdevelopment is analyzed. All the mentioned leading types of activities are supposed to be based on the available level of social reality modeling in each of the considered ages. It is specified that the general undifferentiated model of the world is formed in infancy within the child’s inclusiveness in human dialogue, the model varies in the degree of stability / instability, trust / threat; in preschool childhood the modeling activity allows to carry out the primary semantic marking of external and internal reality; at teenage age there is a shift of the semantic marking of the world and its realization at a new level provided with the developing high mental functions. In relation to each analyzed type of the modeling activity the conclusion about its potential for personal development and self-development is made.